Pemanfaatan Media Youtube dalam Pembelajaran Keterampilan Membaca Teks Puisi - Vivi Anjelita; Syahrul Ramadhan (Intellektika : Jurnal Ilmiah Mahasiswa, 2026)
This study aims to describe the utilization of YouTube media in teaching poetry reading skills among eleventh-grade students at MAN 1 Kota Padang. The study employed a quantitative approach using a descriptive survey method. The research sample consisted of 85 students from classes XI.F2 to XI.F7 selected through purposive sampling. Data were collected through a questionnaire consisting of 10 statement items using a four-point Likert scale, namely Strongly Agree, Agree, Disagree, and Strongly Disagree. The collected data were analyzed using descriptive quantitative analysis through percentage calculations to identify students’ responses toward the use of YouTube media in poetry reading instruction. The findings revealed that most students showed positive responses to the use of YouTube, particularly in helping them understand poetry reading techniques, intonation and expression, increasing learning interest, enhancing self-confidence in reading poetry in front of the class, and making the learning process more engaging and less monotonous. In addition, most students perceived poetry reading instruction through YouTube as easier to understand compared to conventional learning methods. Therefore, YouTube media can be utilized as an effective learning medium to support poetry reading skills among eleventh-grade students at MAN 1 Kota Padang.